Effect of High-Intensity Interval Training on Body Composition, Cardiorespiratory Fitness, Blood Pressure, and Substrate Utilization During Exercise Among Prehypertensive and Hypertensive Patients With Excessive Adiposity - Delgado-Floody, Pedro; Izquierdo, Mikel; Ramírez-Vélez, Robinson; Caamaño-Navarrete, Felipe; Moris, Roberto; Jerez-Mayorga, Daniel; Andrade, David C.; Álvarez, Cristian (Frontiers in Physiology, 2020)
Regular exercise training is a recognized lifestyle strategy to lower resting blood pressure (BP), but little is known about substrate metabolism in population with high BP. Thus, the purpose of this study was to investigate the effects of 16-weeks of HIIT on body composition, BP, cardiorespiratory fitness by V.O2max, and substrate utilization during exercise among prehypertensive and hypertensive patients with excessive adiposity. We also aimed to test the potential association between changes in cardiorespiratory fitness, substrate utilization during exercise and BP. Forty-two physically inactive overweight/obese participants participated in 16-weeks of HIIT intervention. The HIIT frequency was three times a week (work ratio 1:2:10, for interval cycling: rest period: repeated times; 80–100% of the maximum heart rate). Groups were distributed based on their baseline BP: HIIT-hypertensive (H-HTN: age 47.7 ± 12.0 years; body mass index [BMI] 30.3 ± 5.5 kg/m2; systolic [SBP]/diastolic BP [DBP] 151.6 ± 10/81.9 ± 4.2 mmHg), HIIT-pre-hypertensive (H-PreHTN: age 37.6 ± 12.0 years; BMI 31.9 ± 5.3 kg/m2; SBP/DBP 134.4 ± 3.2/74.9 ± 7.0 mmHg), and a normotensive control group (H-CG: age 40.7 ± 11.0 years; BMI 29.5 ± 4.2 kg/m2; SBP/DBP 117.0 ± 6.2/72.4 ± 4.1 mmHg). Anthropometry/body composition, BP, and metabolic substrate utilization during exercise (fat [FATox], carbohydrate [CHOox] oxidation, respiratory exchange ratio [RER], and V.O2max), were measured before and after the 16-week HIIT intervention. Adjusted mixed linear models revealed a significant improved in V.O2max were + 3.34 in the H-CG, + 3.63 in the H-PreHTN, and + 5.92 mL⋅kg–1⋅min–1, in the H-HTN group, however, the Time × Group interaction were not significant (p = 0.083). All the exercise types induced similar decreases on SBP (−8.70) in the H-HTN, (−7.14) in the H-CG, and (−5.11) mmHg in the H-PreHTN, as well as DBP levels (−5.43) mmHg in H-CG group (p = 0.032 vs. H-HTN group). At 16-week, no significant correlations were noted for the changes of blood pressure, cardiorespiratory fitness or exercise metabolism substrates outcomes. In conclusion, our results suggest that a 16-week HIIT-intervention improved V.O2max and blood pressure BP, but these changes are independent of substrate utilization during exercise in normotensive and hypertensive participants with excessive adiposity.